SISTEM PENDUKUNG KEPUTUSAN PENERIMA BEASISWA PRESTASI PADA SMK PENCAWAN MEDAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Demastra Persada Sitepu (UPPM, 2018)
Scholarships are a form of appreciation for both students and students while undergoing education. In accordance with the regulations set by Medan Pencawan Vocational School to get a scholarship, the criteria required to determine the scholarship are determined, then a Decision Support System with the Simple Additive Weighting (SAW) method is needed. The study was conducted by finding the weight value for each criterion, and then making a ranking process that would determine the optimal alternative is the best student will be considered by the decision maker to get a scholarship